Clinical Predictors of Neurocognitive Status in Children With Chronic Kidney Disease: Neurocognitive Status in Chronic Kidney Disease - Roy , Ranjit Ranjan; Begum , Afroza; kaniz, Kaniz Fatema; Hauque, Saimul; Akter, Amina; Shaheen Akhter (Journal of Pediatric Nephrology, 2022)
Background and Aim: Chronic kidney disease (CKD) is often associated with a variety of cognitive deficits. This will have significant lifelong implications. Therefore, we measure the clinical predictors of cognitive impairment. Methods: This cross-sectional study was conducted in a third-level hospital from October 2017 to December 2018. A total of 41 patients with CKD stage III to V and V on dialysis, aged 6 to 14 years of both sexes were included in this study. CKD was staged according to the estimated glomerular filtration rate (eGFR). The Wechsler intelligence scales for childrenrevised (WISC-R) were provided as an individualized measure of verbal and performance abilities. Then individual score was compared among the study population. Results: A total of 41 patients were studied. The Mean±SD age was 10.35±2.19 years. The majority were male (56%) and the male-to-female ratio was 1.3:1. Full-scale intelligence quotient (IQ) deficits were found in 31 patients (75.6%) and most of them had mild cognitive deficits (96.8%). Among them, verbal IQ deficit was found in 7 patients (17.1%), performance IQ deficit in 6(14.6%), and combined IQ deficit in 18(43.9%). IQ score did not depend on the severity of the disease. The duration of the disease was longer and the age at initiation of renal replacement therapy (RRT) was lower, for those with the cognitive deficit, was not significant. School attendance and performance were significantly poor in cognitive deficit patients but anemia and hypertension had no significant impact. Conclusion: The mild cognitive deficit was often associated with childhood CKD but not related to the severity of the disease. Therefore, the cognitive function should be routinely screened and monitored during the evaluation of children with CKD.